ANALISIS DUKUNGAN SOSIAL MASYARAKAT TERHADAP KESEJAHTERAAN KELOMPOK RENTAN - Pradini, Aufa Ema; Septian, Bunga; Shamara, Devina; Reyhan, Edowardo; Anggraini, Putri; Daffa , Wijdan (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
This research focuses on social support for the elderly in Gadingkulon Village, Dau District, Malang. The research conducted at this time uses a descriptive qualitative method in which the approach uses the concept of social exchange theory by George C. Homans. As well as the data collection technique that was used this time used several techniques including observation, in-depth interviews, documentation, and reinforced by literature studies that are relevant to the discussion in the research. This study aims to find out how the condition of the elderly group and find out what kind of social support is given to the elderly group in Gadingkulon Village, Dau District, Malang City. From this research some results were obtained; the condition of the elderly group which includes decreased immunity and health, economic problems due to reduced income in a family, residential patterns of the elderly who live in their own homes, and lack of social support for the elderly from both the family and the surrounding environment. However, based on the research that has been done, shows that progress has been made with the creation of programs as a form of social support for the elderly. This is evidenced by the existence of assistance from the government in the form of PKH money and the BPJS program and the existence of an elderly Posyandu program which is carried out once a month. Keywords:  Social Support, Social Welfare, Vulnerable Group